PENERAPAN NILAI-NILAI ISLAM DALAM PEMBELAJARAN AKIDAH AKHLAK DI SEKOLAH MENENGAH ATAS MUHAMMADIYAH 3 WAKTU KELIR SUKOHARJO TAHUN PELAJARAN 2024/2025 - Joko Subando; Fajarullah Al Ghifari (JIPDAS (Jurnal Ilmiah Pendidikan Dasar), 2025)
This research was carried out at SMA Muhammadiyah 3 Watu Kelir Sukoharjo, to reveal the application of Islamic values in learning moral beliefs. This research uses observation by systematically observing and recording the symptoms that appear on the research object. Observations and recordings carried out on objects include observing the process of student and teacher activities while at school, observing the process of applying Islamic values in learning moral beliefs, and observing student behavior. With this research, it is hoped that it will help create the school's vision and mission so that students will have good morals, be broad in knowledge of religion and general knowledge, become hafidz hafidzah of the Qur'an, religious, Mubasyarah (get along well in society), have a firmly held faith, be able to practice knowledge in everyday life and achieve achievements.